Intermittent running at vVO2max allows to sustain a longer time at VO2max that severe continuous submaximal run - Billat, V. L; Bocquet, V.; Slawinski, J.; Demarle, A.; Lafitte, L.; Chassaing, P.; Koralsztein, J. P. (1999)
This investigation compared time sustained at VO2max in exhaustive exercise under two protocols: 30-30 second intermittent run at 100% VO2max and then 50% VO2max; and a continuous run at lactate threshold velocity (vLT) plus 50% of the difference between vVO2max and vLT. Ss were long distance runners (N = 9) unfamiliar with intermittent training. Intermittent work provided greater time at VO2max and lower blood lactates than in continuous training. Implication. Work volumes at VO2max are extended with intermittent training over those achieved with continuous training. Medicine and Science in Sports and Exercise, 31(5), Supplement abstract 275